Demographic and Psychological Characteristics of Tribal Farmers TowardsSoil and Water Conservation Technologies–A Case Study of NandurbarDistrict of Maharashtra (Indian Journal of Extension Education, 2011)
The majority of tribals in Nandurbar district of Maharashtra were poor farmers, illiterate, having small size of land holdings with annual income less than rupees five thousand. The tribal farmers were having big size of family with 6 to 10 or more family members and their staple food was Sorghum chapati with Urd dal (Black gram) or chatani (powder of dry red chilies with salt). The tribal farmers were migrating in nearby areas to earn their income by doing labour work in fields of other farmers. The majority of tribal farmers were having low socio-economic status i.e. lack of implements, equipments, irrigation facilities, mechanical power, animal power and material possession. The tribal farmers were very much dependent on forest for firewood for cooking food and timber wood for their Charpai and house making particularly in roof. They were also collecting Mahuda flowers from forest area for their domestic uses and Timbru leaves for Bidi making for their own smoking purpose. The tribal farmers in Nandurbar district of Maharashtra were having moderate to low level of knowledge and adoption of different soil and water conservation (SWC) technologies due to reason of their poor socio-economic status they were unable to adopt costly SWC technologies.